The method of scholar " Yaḥya Ibn-Aḥmad Ibn-Muẓaffar" in weighting and reasoning in his book "Al-Kawakib Al-Naiyira Al-kashifa li-Maanai Al-tadkira" "Book of Al- Eibadat Enmudhajan" - Al-Gabri, Fawakha Saleh (Journal of Islamic Sciences, 2023)
The aim of this research is to introduce the scholar Yahya bin Mudhaffar Al-Sana'ani and his methodology in weighting and reasoning. The methodology of this research was the inductive approach, the descriptive approach, and the historical approach. This research consists of two axes: In the first axis, I dealt with: introducing the scholar Yahya bin Mudhaffar Al-Sana’ani, and dealt with in the second axis: the scholar’s approach Yahya Ibn Muzaffar Al-Sana'ani in Weighting and Inference. The most important results of this research: It is: that the author, the scholar and jurist Yahya bin Ahmed bin Muzaffar Al-Sana'ani, a fundamentalist jurist, Great science has many books. Also, Ibn Muzaffar used many formulas to give weight to the sayings in matters, in addition to that he inferred his preferences from the Holy Qur’an, the Sunnah of the Prophet, and some fundamental rulings. Basic vocabulary: Ibn Muzaffar's approach, inference and weight, the bright planets.
Keywords: Investigation; Conclusion; Jurisprudence; Ibn Muzaffar 's approach; Literature